A Phone-Based Early Psychological Intervention for Supporting Bereaved Families in the Time of COVID-19 - Borghi, Lidia; Menichetti, Julia; Vegni, Elena; , The Early Bereavement Psychological Intervention working group (Frontiers in Public Health, 2021)
The exceptional circumstances of the Coronavirus disease (COVID-19) pandemic are making the grief processes challenging for families who are losing a relative for COVID-19. This community case study aimed to describe a phone-based primary preventive psychological intervention that has been delivered to these families by the Clinical Psychology unit of an Italian hospital. In particular, the article reports how the intervention has been organized within the overall hospital care pathway for families, the specific contents and components of the intervention, and the seven-phase structure of the intervention. The unique features and related challenges of the intervention, along with the implications for clinical practice, are discussed.